2015
DOI: 10.1371/journal.pone.0131652
|View full text |Cite
|
Sign up to set email alerts
|

Matrix M H5N1 Vaccine Induces Cross-H5 Clade Humoral Immune Responses in a Randomized Clinical Trial and Provides Protection from Highly Pathogenic Influenza Challenge in Ferrets

Abstract: Background and MethodsHighly pathogenic avian influenza (HPAI) viruses constitute a pandemic threat and the development of effective vaccines is a global priority. Sixty adults were recruited into a randomized clinical trial and were intramuscularly immunized with two virosomal vaccine H5N1 (NIBRG-14) doses (21 days apart) of 30μg HA alone or 1.5, 7.5 or 30μg HA adjuvanted with Matrix M. The kinetics and longevity of the serological responses against NIBRG-14 were determined by haemagglutination inhibition (HI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…The trial was performed in early 2009 at the Haukeland University Hospital in Bergen, Norway, with samples being collected prevaccination (day 0), postvaccination after one dose (day 21), and postvaccination after the second dose (day 42). Additional information for the clinical trial can be found on ClinicalTrials.gov website (NCT00868218) identifier ( 20 , 21 , 38 ).…”
Section: Methodsmentioning
confidence: 99%
“…The trial was performed in early 2009 at the Haukeland University Hospital in Bergen, Norway, with samples being collected prevaccination (day 0), postvaccination after one dose (day 21), and postvaccination after the second dose (day 42). Additional information for the clinical trial can be found on ClinicalTrials.gov website (NCT00868218) identifier ( 20 , 21 , 38 ).…”
Section: Methodsmentioning
confidence: 99%
“…A number of novel adjuvants, such as microcrystalline tyrosine, Matrix M, pathogen-associated molecular patterns, and chitosan, are in development. [111][112][113][114] DNA and RNA vaccines induce an immune response to the nucleic acid-encoded antigen. 115 Impressive results have been reported in animals for a single low-dose intradermal, nonreplicating DNA vaccine for RSV; however, whether this will translate effectively to human subjects is not yet known.…”
Section: Vaccines and Mabsmentioning
confidence: 99%
“…High levels of in vitro erythrocyte binding inhibition (>90%) were achieved with Matrix-M formulations in this study [94]. Additionally, Matrix-M has been assessed in a Phase I clinical study in combination with chimpanzee adenovirus 63 [95]. Similar to Matrix-M, ISCOMs have a mean diameter of ~40 nm; however, this technology incorporates antigens into the ISCOM such that they are displayed in a multimeric fashion on the particles.…”
Section: Aqueous Liposomal Platformsmentioning
confidence: 90%